Dynamic loss comparison between Fixed-State and Reconfigurable Solar Photovoltaic Array - Patnaik, B.; Mohod, J.; Duttagupta, S. P. (2012 38th IEEE Photovoltaic Specialists Conference, 2012)
A Fixed-State Solar Photo-Voltaic array delivers reduced power output when subject to Non-Uniform Illumination conditions. In [1] we have proposed a SPV array reconfiguration scheme which dynamically reconnects the modules based on a Bi-State (BRIGHT/DARK) reconfiguration approach which shows improvement in power output. In [2] the reconfiguration algorithm has been modified to incorporate an additional GREY state in order to better match real-life conditions. This paper compares the power losses between the Reconfigurable array and the Fixed-State array. For a Fixed-State [m×n] SPV array (bypass diodes NOT present) when a string (column) is subject to solar insolation corresponding to BRIGHT, GREY and DARK states, the effective string (column) current will equal the output from the Dark State Modules (since IPV increases with increase in the solar insolation and vice versa). With bypass diodes present (to allow excess flow of current from BRIGHT State and GREY State Modules in the example above), there is still power loss due to the following three factors: a) Voltage drop across each bypass diode that has been activated due to increase in dynamic series resistance of the SPV modules under low solar insolation. The V-I losses are significant if the string (column) current is large. b) Cumulative voltage drops due to multiple activated bypass diodes will shift the string (column) voltage left (lower) on the Power-Voltage (output) characteristics. c) As a consequence of (b), a high-gain, downstream DC-DC converter is required in order to match output load specifications (boost the lowered operating voltage). This is problematic since we have observed that the converter losses increase with increasing conversion ratio. In this report, we examine in detail, the impact of Dynamic Loss Elements for a 4×4 Fixed-State SPV array (bypass diodes and downstream DC-DC converters) vis-à-vis a Tri-State Reconfigurable SPV array (MOSFET switches). The average total energy production by a mono-crystalline SPV array is also shown. A real-time Tri-state algorithm based reconfiguration controller unit helps determine an optimal configuration of the SPV array on the basis of dynamic inputs from module-integrated current (Im, di/dt) and temperature (Tm) sensors. It has been demonstrated that reconfiguration approach leads to a lowering of dynamic losses over a wide range of Non-Uniform Illumination conditions.